2007
DOI: 10.1074/jbc.m706909200
|View full text |Cite
|
Sign up to set email alerts
|

Negative Regulation of Inducible Nitric-oxide Synthase Expression Mediated through Transforming Growth Factor-β-dependent Modulation of Transcription Factor TCF11

Abstract: Inducible nitric-oxide synthase (iNOS) plays a central role in the regulation of vascular function and response to injury. A central mediator controlling iNOS expression is transforming growth factor-␤ (TGF-␤), which represses its expression through a mechanism that is poorly understood. We have identified a binding site in the iNOS promoter that interacts with the nuclear heterodimer TCF11/MafG using chromatin immunoprecipitation and mutation analyses. We demonstrate that binding at this site acts to repress … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
38
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(41 citation statements)
references
References 42 publications
3
38
0
Order By: Relevance
“…ZNF42 induces invasion and in vivo metastasis in colorectal and cervical cancer, at least in part by regulating Axl gene expression (Lu et al, 2010). Transcription factors of TCF11 and MafG form nuclear heterodimer in the regulation of gene transcription mediated by TGF-beta signaling pathway, which is also the pathway that fascin involved (Berg et al, 2007;Mudduluru et al, 2010;Kannan et al, 2012). These results indicated that some migration and metastasis related transcription factors might regulate the DEGs after fascin was knockdown.…”
Section: Discussionmentioning
confidence: 87%
“…ZNF42 induces invasion and in vivo metastasis in colorectal and cervical cancer, at least in part by regulating Axl gene expression (Lu et al, 2010). Transcription factors of TCF11 and MafG form nuclear heterodimer in the regulation of gene transcription mediated by TGF-beta signaling pathway, which is also the pathway that fascin involved (Berg et al, 2007;Mudduluru et al, 2010;Kannan et al, 2012). These results indicated that some migration and metastasis related transcription factors might regulate the DEGs after fascin was knockdown.…”
Section: Discussionmentioning
confidence: 87%
“…A large number of studies have demonstrated that elevated expression of iNOS contribute to increased production of NO; NO is harmful to many tissues and cells and plays an important role in septic shock and other diseases [4][5][6][7][8][36][37][38][39][40]. However, the molecular mechanism that regulates transcriptional expression of iNOS is incompletely defined.…”
Section: Discussionmentioning
confidence: 99%
“…It is conceivable that regulatory mechanisms that control the timing and intensity of NO production by iNOS exist so that protective effects outweigh detrimental ones. The regulation of iNOS expression and the related signal transduction pathways have been well documented in endotoxic shock animal models and various types of cells treated with LPS [4][5][6][7][8]. However, the molecular mechanism involved in regulating transcription of iNOS has not been fully clarified.…”
Section: Introductionmentioning
confidence: 99%
“…In normal wound healing, there is transition of fibroblasts to contractile fibroblasts [myofibroblasts], however, this phenomenon is supressed and there is absence of myofibroblasts in keloid [53,[55][56][57][58]. Transition of fibroblast to myofibroblasts is inhibited by NO [53] and is enhanced by TGFβ.…”
Section: Tgfβ and No Effect On Fibroblast-myofibroblast Transition Inmentioning
confidence: 99%